The inheritance and expression patterns of two classes of retinoblastoma-related genes in the stem of Brassica juncea from both parental genomes - Shi, Hui; Zou, Xiaoxia; Xu, Cheng; Li, Junxing; Liu, Bin; Chen, Liping (Scientia horticulturae, 2014)
•Two RBR genes (RBR1 and RBR2) with 90–91% amino acid identity were isolated from B. rapa and B. nigra, respectively.•The expression level of RBR family members was higher in the stem than in other tissues of B. juncea.•The results suggested that BjuB.RBR.a and BjuA.RBR.a might have specific functions in stem swelling.•However, the results implied BjuB.RBR.b and BjuA.RBR.b might play some basic roles in stem development. In the present study, two classes of retinoblastoma-related (RBR) genes were isolated from Brassica rapa (AA) and B. nigra (BB). These genes were defined as BraA.RBR.a, BraA.RBR.b in B. rapa and BniB.RBR.a, BniB.RBR.b in B. nigra, and 91 and 90% identity were shared at the amino acid level. Interestingly, alternative splicing was also observed both in BraA.RBR.a and BniB.RBR.a transcripts, which consequently yielded two proteins with different C-termini. In the allotetraploid B. juncea (AABB), the corresponding parental RBR loci were maintained, but they experienced a different evolutionary pattern. BjuB.RBR.b and BjuA.RBR.b were found to contain more base mutations and deletions/insertions than BjuB.RBR.a and BjuA.RBR.a when compared with their counterparts in the presumed parents. A comparison of the transcript levels in various tissues suggests a different expression pattern between RBR1 (BraA.RBR.a, BniB.RBR.a) and RBR2 (BraA.RBR.b, BniB.RBR.b); the former varied in expression among different tissues, whereas the latter was almost constitutively expressed. In B. juncea, we found that four RBR genes from both the A- and B-subgenomes were expressed in the tissues tested, suggesting absence of uniparental silencing of RBR genes. The transcript changes of the RBR family during stem development in tuber mustard (B. juncea (L.) Czern. et Coss. var. tumida Tsen et Lee) were also investigated to find its possible roles involved in this process. The results indicated that expression of BjuB.RBR.a and BjuA.RBR.a peaked in stages III and IV when the stems grow vigorously, which suggested that these genes might perform a specific function in stem swelling, and the constitutive expression of BjuB.RBR.b and BjuA.RBR.b might imply their basic roles in stem development. The lack of parental bias and the altered expression pattern of the two RBR classes from the parents suggest that the RBR members might undergo a subfunctionalisation or neofunctionalisation and that these genes might play important roles in the cell-cycle regulation involved in the stem-swelling process of tuber mustard.